(3GdeSFhdjI GdLfGFjI GdfGTFI Yf fbd GdYOhi (B/ s - (3eMeO LHQjd EHQGgje MSfs; (3TQja SjO cGed s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
{u(3FEF4(B}{u(3FEBC(B}{u(3FECC(B}{u(3FE8F(B} {u(3FE87(B}{u(3FE9C(B}{u(3FE92(B}{u(3FE8E(B}{u(3FE95(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FED8(B}{u(3FEBC(B}{u(3FEA9(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FEA0(B}{u(3FEE8(B}{u(3FE8E(B}(3Fi (B{u(3FED3(B}{u(3FEF4(B}{u(3FEEC(B}{u(3FE8E(B}: (3ceG (B{u(3FECB(B}{u(3FEAD(B}{u(3FEC0(B}{u(3FE95(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FEAD(B}{u(3FEB4(B}{u(3FE8E(B}{u(3FEDF(B}{u(3FE94(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FEE4(B}{u(3FEB4(B}{u(3FE8C(B}{u(3FEED(B}{u(3FEDF(B}{u(3FEF4(B}{u(3FE94(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FEA0(B}{u(3FEE8(B}{u(3FE8E(B}{u(3FE8C(B}{u(3FEF4(B}{u(3FE94(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FEE8(B}{u(3FE8E(B}{u(3FEB8(B}{u(3FE8C(B}{u(3FE94(B} {u(3FECB(B}{u(3FEE5(B} {u(3FEE8(B}{u(3FED8(B}(3d (B{u(3FE8D(B}{u(3FEDF(B}{u(3FECC(B}{u(3FEA9(B}{u(3FEED(B}{u(3FEEF(B} {u(3FE92(B}{u(3FEC1(B}{u(3FEAD(B}{u(3FEF4(B}{u(3FED5(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FEA8(B}{u(3FEC1(B}{u(3FE84(B}: {u(3FEED(B} {u(3FE98(B}{u(3FECC(B}{u(3FEAD(B}{u(3FEF4(B}{u(3FEBD(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FED0(B}{u(3FEF4(B}{u(3FEAD(B} {u(3FEDF(B}{u(3FEE0(B}{u(3FEA8(B}{u(3FEC1(B}{u(3FEAD(B} (3ai (B{u(3FEE4(B}{u(3FEA0(B}{u(3FE8E(B}(3d (B{u(3FE8D(B}{u(3FEDF(B}{u(3FECC(B}{u(3FEFC(B}{u(3FED7(B}{u(3FE94(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FEAF(B}{u(3FEED(B}{u(3FEA0(B}{u(3FEF4(B}{u(3FE94(B}: {u(3FEED(B} (3ai (B{u(3FE8D(B}{u(3FEDF(B}{u(3FEA4(B}{u(3FEE4(B}(3d (B{u(3FEED(B} {u(3FE8D(B}{u(3FEF9(B}{u(3FEE8(B}{u(3FEA0(B}{u(3FE8E(B}{u(3FE8F(B}: {u(3FEED(B} (3ai (B{u(3FE98(B}{u(3FECC(B}{u(3FEAD(B}{u(3FEF4(B}{u(3FEBD(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FED0(B}{u(3FEF4(B}{u(3FEAD(B} {u(3FEDF(B}{u(3FEE0(B}{u(3FEA8(B}{u(3FEC1(B}{u(3FEAD(B} (3ai (B{u(3FE8D(B}{u(3FEF7(B}{u(3FEB8(B}{u(3FEA8(B}{u(3FE8E(B}{u(3FEB9(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FEE4(B}{u(3FECC(B}{u(3FEE8(B}{u(3FEED(B}{u(3FEF4(B}{u(3FE94(B}s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3HHdjhLQGajG(B: (3UaMGJ (B338-365s
Keywords: (3GdfUhU GdJTQjYjI GdefXeI dfbd GdYOhjs; (3GdQcf GdeGOj aj aYd fbd YOhj GdCeQGV GdeYOjIs; (3fbd GdYOhis; (3GdfJjLI GdELQGejI daYd fbd YOhj GdCeQGV GdeYOjIs; (3GdQcf GdeYfhj dJLQje aYd fbd YOhj GdCeQGV GdeYOjIs; (3GdeSFhdjI GdLfGFjI GdfGTFI Yf fbd GdYOhj HWQjb GdNWCs; (3JWHjbGJ GdNWC GdWHj aj eLGd fbd YOhj GdCeQGV GdeYOjIs; (3QGHWI GdSHHjI aj JLQje aYd fbd GdYOhjs; (3fbd GdYOhj Yf WQjb GdTNU GdeYfhjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs